Informed Arguments A Guide to Writing and Research - Pantuso, Terri; LeMire, Sarah; Anders, Kathy (Open textbook library., 2022)
Welcome to composition and rhetoric! While most of you are taking this course because it is required, we hope that all of you will leave with more confidence in your reading, writing, researching, and speaking abilities as these are all elements of freshman composition. Many times, these elements are presented in excellent textbooks written by top scholars. While the collaborators of this particular textbook respect and value those textbooks available from publishers, we have been concerned about students who do not have the resources to purchase textbooks. Therefore, we decided to put together this Open Educational Resource (OER) explicitly for use in freshman composition courses at Texas A&M University. It is important to note that the focus for this text is on thesis-driven argumentation as that is the focus of the first year writing course at Texas A&M University at the time of development. However, other first year writing courses at different colleges and universities include a variety of types of writing such as personal essays, informative articles, and/or creative writing pieces. The collaborators for this project acknowledge each program is unique; therefore, the adaptability of an OER textbook for first year writing allows for academic freedom across campuses.